Full-length transcriptome sequencing analysis and development of EST-SSR markers for the endangered species Populus wulianensis - Wu, Qichao (Sci Rep, 2020)
Populus wulianensis is an endangered species endemic to Shandong Province, China. Despite the economic and ornamental value of this species, few genomics and genetic studies have been performed. In this study, we performed a relevant analysis of the full-length transcriptome sequencing data of P. wulianensis and obtained expressed sequence tag (EST)-simple sequence repeat (SSR) markers with polymorphisms that can be used for further genetic research. In total, 8.18 Gb (3,521,665) clean reads with an average GC content of 42.12% were obtained. From the corrected 64,737 high-quality isoforms, 42,323 transcript sequences were obtained after redundancy analysis with CD-HIT. Among these transcript sequences, 41,876 sequences were annotated successfully. A total of 23,539 potential EST-SSRs were identified from 16,057 sequences. Excluding mononucleotides, the most abundant motifs were trinucleotide SSRs (47.80%), followed by di- (46.80%), tetra- (2.98%), hexa- (1.58%) and pentanucleotide SSRs (0.84%). Among the 100 designed EST-SSRs, 18 were polymorphic with high PIC values (0.721 and 0.683) and could be used for analyses of the genetic diversity and population structure of P. wulianensis. These full-length transcriptome sequencing data will facilitate gene discovery and functional genomics research in P. wulianensis, and the novel EST-SSRs developed in our study will promote molecular-assisted breeding, genetic diversity and conservation biology research in this species.